A novel system of biomass for the generation of inherently separated syngas by combining chemical looping CO2-gasification and steam reforming process. (1st January 2022) - Sun, Haochen; Wang, Zhiqing; Fang, Yitian; Liu, Zheyu; Dong, Libo; Zhou, Xing; Yu, Zhongliang; Li, Xiangyu; Bai, Jin; Huang, Jiejie
Highlights: Inherently separated syngas was generated during the FCG process. CO2 conversion, biomass utilization are expected to realize through FCG process. Initial CO2 concentration was crucial to the gas generation during the FCG process. An inflection point of initial CO2 concentration was found. A syngertic effect between OC and CO2 on tar elimination was found. Abstract: The utilization of biomass and CO2 has become very important for solving environmental problems all over the world. In this study, a novel Fe-based CO2 -gasification (FCG) process of biomass which combining chemical looping CO2 gasification and steam reforming process is proposed. The effects of experimental parameters including biomass/oxygen carrier (B/OC) ratio and initial CO2 concentration on the performance of the gas, liquid and solid products were analyzed in detail. The results show that CO2 has an opposite effect on the oxygen transfer capacity (OTC) of OC and carbon conversion rate, which results in an inflection point of initial CO2 concentration at around 20%: larger than this value, only a little hydrogen is generated, and once the concentration lower than this value, the yield of hydrogen dramatically increases. Moreover, the carbon conversion rate encountered a slight decline at the inflection point. As for the generation of tar, CO2 and OC have a synergetic effect on tar cracking: CO2 promotes the cracking of heavy tar and OC reduces the production of light tar effectively, and thus a better effect of tar cracking can be obtained when both OC and CO2 exist. This process can generate inherently separated syngas (CO-rich gas and high purity of H2 ), reduce the amount of undesired tar, utilize CO2 and Fe-containing solid waste, and thus this process is expected to have an extensive prospect for industrial application.